Nurses specialised in wound, ostomy, and continence care: self-care during the Novel Coronavirus (COVID-19) pandemic - Janet L Kuhnke, & Cathy Harley and & Tracy Lillington (WCET Journal - Chinese Edition, 2021)
Nurses specialised in wound, ostomy and continence (NSWOCs) who are working during a pandemic require engagement in self-care. Nurses across all sectors – clinical practice, education, leadership, policy, research and service – are each deeply aware of the burden of COVID-19, and provide the best care when they engage in self-care activities. Recent COVID-19 studies evaluating the mental health and well-being of staff working in the pandemic are of concern as staff are burdened by pandemic demands. Mental health and well-being, as well as skin and eye care, are essential. This paper talks about the Canadian perspective.